(untitled) (NTU journal for Administrative and Human Sciences (JAHS), 2023)
Current research sought to identify the contribution of the organizational health dimensions (institutional coherence, manager influence, academic aspects, and morale) in enhancing the quality of the education service at the colleges and institutes of the Northern Technical University in Nineveh Governorate, The objective of the research is to provide a theoretical framework based on the organizational health dimensions linked to the Northern Technical University (NTU), the educational service quality dimensions, and the testing of the correlation and impact between research variables through the distribution of (46) questionnaires , These questionnaires were analyzed using the statistical program SPSS.Ver-28, and a number of conclusions were then drawn, the most significant being that the assumptions made in the research were correct by establishing a significant correlation between the research variables, In addition, the moral impact of the organizational health dimensions on the educational service quality dimensions reflects the university’s interest in adopting these dimensions and aligning the nature of the university’s work with the research variables , A number of suggestions were submitted, the most important of which was "disseminating the concepts of the organizational health and educational service quality dimensions among university staff by organizing educational campaigns and training courses in this field with a view to strengthening and enhancing organizational health and educational service quality dimensions", which could contribute to raising the level of educational service quality at the university.